The Effect of Controlled Decompression for Severe Traumatic Brain Injury: A Randomized, Controlled Trial - Chen, Junhui; Li, Mingchang; Chen, Lei; Chen, Weiliang; Zhang, Chunlei; Feng, Yi; Wang, Yuhai; Chen, Qianxue (Frontiers in Neurology, 2020)
Background Experimental evidence has indicated the benefits of intraoperative controlled decompression for the treatment of severe traumatic brain injury (sTBI). Intraoperative rapid decompression (conventional decompression) for the treatment of sTBI may result in intra- and postoperative complications. Controlled decompression may reduce these complications. Previous clinical trials in China have not yielded conclusive results regarding controlled decompression for sTBI. Therefore, we explored whether controlled decompression treatment decreases the rates of complications and improves the outcomes of patients with sTBI. METHODS We performed this randomized, controlled trial at our hospital. Patients with sTBI aged 18 to 75 years old were randomly (1:1) divided into controlled decompression surgery (n=124) or rapid decompression surgery groups (n=124). The primary outcome measures were the Extended Glasgow Outcome Scale (GOS-E) score at 6 months and 30-day all-cause mortality. The secondary outcomes were the incidences of intraoperative brain swelling, posttraumatic cerebral infarction, and delayed hematoma. RESULTS Compared with the rapid decompression group, the controlled decompression group had reduced 30-day all-cause mortality (18.6% vs 30.8%, P=0.035) and improved the 6-month GOS-E scores, and the difference was significant. In addition, the patients in the controlled decompression group had a lower intraoperative brain swelling rate (13.3% vs 24.3%, P=0.036), a lower delayed hematoma rate (17.7% vs 29.0%, P=0.048) and a relatively lower posttraumatic cerebral infarction rate (15.0% vs 22.4%, P=0.127) than those in the rapid decompression group. CONCLUSIONS Our data suggest that controlled decompression surgery significantly improves sTBI outcomes and decreases the rates of sTBI-related complications. However, this was a single-hospital study, and well-designed multicenter randomized controlled trials are needed to evaluate the effects of controlled decompression surgery for the management of patients with sTBI. Trial registration Chinese Clinical Trial Registry; Date: 14/Dec/2013; Number: ChiCTR-TCC-13004002. Level of Evidence Therapeutic/Care Management Study, Level III.